Blood Pressure Recordings During Hemodialysis Access Interventions: Implications for Acute Management. Issue 4 (28th March 2013) - Asif, Arif; Castro, Hector; Waheed, Ahmed Ameen; Kumar, Vishesh; Haqqie, Syed S; Siskin, Gary; Mathew, Roy O; Mason, Darius; Vachharajani, Tushar; Nayer, Ali; Merrill, Donna; Akmal, Muhammad UT; et al.
Abstract: A retrospective study evaluating the pattern of blood pressure and its related complications before, during, and after percutaneous hemodialysis interventions was performed in patients presenting with asymptomatic hypertension. Hemodialysis patients undergoing percutaneous interventions including tunneled hemodialysis catheter insertion, percutaneous balloon angioplasty and thrombectomy procedure, and stage II hypertension (systolic blood pressure ≥160 mmHg) were included in this analysis. Blood pressure medications were not used while midazolam and fentanyl were routinely administered. Patients were followed for up to 4 weeks to monitor any complications. The mean blood pressure before, during, and after the procedures were 185 ± 18/96 ± 14, 172 ± 22/92 ± 15, and 153 ± 25/87 ± 14, respectively. There was a statistically significant difference between the blood pressure readings before and after the procedure (before = 185 ± 18/96 ± 14, after = 153 ± 25/87 ± 14; p  = 0.001). None of the patients had a stroke, myocardial infarction, or acute pulmonary edema before, during, or after the procedure or during the 4‐week follow‐up period. A significant reduction in blood pressure was observed after the procedure without the administration of any antihypertensive medication. These results suggest that the reduction in blood pressure observed after percutaneous dialysis access interventions (particularly in the presence of midazolam and fentanyl) may make it unnecessary to treat asymptomatic hypertension prior to these procedures.